1972
DOI: 10.1111/j.1476-5381.1972.tb08105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of McN‐A‐343 and DMPP on the uptake and release of 3H‐noradrenaline by guinea‐pig atria

Abstract: , responses of atria to noradrenaline were increased and those to tyramine were decreased. 5. DMPP had positive inotropic and chronotropic actions on atria, and these effects were accompanied by an increase in efflux of radioactivity from atria previously incubated with (-)-3H-noradrenaline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…This is a potentially important site of blockade, in view of the recent suggestion that nicotinic drugs require to be transported intraneuronally by the noradrenaline uptake mechanism, as a prerequisite to effecting transmitter release (Su & Bevan, 1970;Bevan & Su, 1972;Allen et al, 1972). If such a mechanism were operating for DMPP in the rabbit heart, then it could be argued that cocaine, McN-A-343 and AHR 602 were inhibiting its effect by blocking its intraneuronal access.…”
Section: Estimation Of Noradrenalinementioning
confidence: 99%
“…This is a potentially important site of blockade, in view of the recent suggestion that nicotinic drugs require to be transported intraneuronally by the noradrenaline uptake mechanism, as a prerequisite to effecting transmitter release (Su & Bevan, 1970;Bevan & Su, 1972;Allen et al, 1972). If such a mechanism were operating for DMPP in the rabbit heart, then it could be argued that cocaine, McN-A-343 and AHR 602 were inhibiting its effect by blocking its intraneuronal access.…”
Section: Estimation Of Noradrenalinementioning
confidence: 99%
“…Although McN-A-343 inhibits noradrenaline uptake in the atria, 10-5 M producing about 50% inhibition (Allen et al, 1972), this concentration had no effect on the responses of the artery to injections of noradrenaline (Rand & Varma, 1971). …”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that McN-A-343 is a potent inhibitor of [3 HI -noradrenaline uptake by guinea-pig atria, and that this action was atropine-insensitive (Allen, Rand & Story, 1972 …”
Section: Reported Thatmentioning
confidence: 99%
“…-Two cholinomimetic drugs, DMPP (N,N-dimethyl-N'-phenylpiperazinium) and McN-A-343 (4-(mchlorophenylcarbamoyloxy) -2 -butynyltrimethylammonium) are potent inhibitors of the uptake of noradrenaline by guineapig atria (Allen, Rand & Story, 1972). In isolated artery preparations, these drugs can cause increases or decreases in responses to sympathetic nerve stimulation, the particular effect depending on the frequency of stimulation and the concentration of drug (Malik & Ling, 1969a;Rand & Varma, 1971).…”
mentioning
confidence: 99%
“…Methods.-The uptake of 3H-( + )-noradrenaline by guinea-pig atria and the effects of drugs on the uptake were measured as described by Allen et al (1972). Atria were incubated with 3H-(+)-noradrenaline (13 X 1O-7M, 05 ,uCi/ml) in Krebs-Henseleit solution at 370 C for 20 minutes.…”
mentioning
confidence: 99%